Facilidades turísticas y oferta en el cantón Pallatanga provincia de Chimborazo - Alexis Mauricio, Guamán Criollo (2021)
ABSTRACT The purpose of this research is to analyze the influence of tourist facilities with the offer of the Pallatanga city of Chimborazo province. The methodology has a quantitative approach, cross-sectional and non-experimental methodological design, the types of research such as: correlational, descriptive and explanatory were applied, in addition to this, the survey technique and the questionnaire instrument were used to collect information data. a convenience sampling for the independent variable tourist facilities (main authorities and workers of the tourism unit of the GAD of the municipality of Pallatanga) and for the dependent variable supply (service providers of the Pallatanga city). With the data obtained, some statistical methods such as Cronbach's Alpha were used to verify the reliability of the instruments, as well as the SPSS V25 statistic that allowed the analysis and interpretation of the results, from which the general and specific hypotheses were verified by means of the chi-square statistical tool, concluding that there is no significant influence between tourist facilities and supply in the Pallatanga city, as well as its components; However, the situational diagnosis showed that the existing tourist facilities in the canton are insufficient, which creates a limiting factor for tourist activity in the city, this leads to little development of tourism, therefore the creation of a plan that will be support for tourism recovery, which will allow to promote tourism and contribute to its development. Keywords: tourist facilities, offer, tourist services, tourist activities, facilities, satisfaction Reviewed by: Lcda. Diana Carolina Chávez Guzmán English Professor. c.c. 0650037955